Individual behavioural counselling for smoking cessation. - Lancaster, T; Stead, L (2002)
BACKGROUND: Individual counselling from a smoking cessation specialist may help smokers to make a successful attempt to stop smoking. OBJECTIVES: The objective of the review is to determine the effects of individual counselling. SEARCH STRATEGY: We searched the Cochrane Tobacco Addiction Group trials register for studies with counsel* in any field. Date of the most recent search: February 2002. SELECTION CRITERIA: Randomised or quasi-randomised trials with at least one treatment arm consisting of face to face individual counselling from a health care worker not involved in routine clinical care. The outcome was smoking cessation at follow-up at least six months after the start of counselling. DATA COLLECTION AND ANALYSIS: Both reviewers extracted data. The intervention and population, method of randomisation and completeness of follow-up were recorded. MAIN RESULTS: We identified eighteen trials. Fifteen compared individual counselling to a minimal intervention, four compared different types or intensities of counselling. Individual counselling was more effective than control. The odds ratio for successful smoking cessation was 1.62 (95% confidence interval 1.35 to 1.94). We failed to detect a greater effect of intensive counselling compared to brief counselling (odds ratio 0.98, 95% confidence interval 0.61 to 1.56). REVIEWER'S CONCLUSIONS: Smoking cessation counselling can assist smokers to quit.